Preparation and catalysis in epoxidation of allyl chloride of zeolitic titanosilicate-1/smectitic clay minerals - Xia, H.; Zhou, C.; Tong, D.; Chen, J.; Yu, W.; Liu, Shaomin (Elsevier BV, 2011)
The composites of zeolitic titanosilicate-1 crystals in a clay matrix (TS-1@clay minerals) were prepared by hydrothermal treatment of a mixture of TS-1 precursor and smectitic clay minerals. Montmorillonite (mmt), hectorite (hct) and fluorohectorite (Fhct) were used and the organic template in the as-synthesized TS-1@clay minerals was removed by calcination at 550 °C for 10 h. The samples were characterized by powder X-ray diffraction (PXRD), Fourier transform infrared (FT-IR) spectrometer, UV–vis diffuse reflectance spectrometer (UV–vis), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The catalytic performances of the resulting composites were evaluated in catalytic epoxidation of allylchloride with hydrogen peroxide (H2O2). The results revealed that the nucleation and growth of TS-1 crystals still occurred in the presence of delaminated clay minerals and consequently the sizes of TS-1 crystals in TS-1@clay mineral composites ranged from 55 to 85 nm, much smaller than those of pure TS-1 obtained from conventional preparation. The presence of fluorohectorite promoted the preferential growth of (020) planes of TS-1 crystals. The existence of trace impurities, in particular LiF in as-made fluorohectorite minerals had a significant adverse effect on catalytic activity. The removal of trace impurities in clay minerals can markedly improve the catalytic properties of the TS-1@Fhct composites in the selective epoxidation of allylchloride with H2O2. Over the composite catalysts prepared with purified Fhct, the catalytic conversion of allylchloride was 68.4% with a 97.3% selectivity to epichlorohydrin.